Modeling of the Stress-Strain State of Through-Reinforced Concrete Structures with External Sheeting Reinforcement by the Finite Element Method - Storozhenko, Leonid; Pents, Volodymyr; Nesterenko Sr., Tetyana; Mahas, Nataliia (International Journal of Engineering and Technology, 2018)
The article deals with the research of the stress-strain state of through- reinforced concrete structures with external sheeting reinforcement by the finite element method (FEM), the comparison of the results of numerical modeling with the results of the physical experiment of testing of through- reinforced concrete structures with external sheeting reinforcement for bending and compression Â Â